The Development of a Simplified Lighting Assessment Tool for Health and Well-being Based on the SOOK Building Standard - Hengrasmee, Nichakorn; Chaiyakul, Yingsawad (Journal of Architectural/Planning Research and Studies (JARS), 2025)
The process of designing lighting to promote health and well-being typically requires the knowledge of specialists who are responsible for designing and carrying out initial assessments. These assessments require the use of mathematics, measurements, and careful consideration of the completed designs or construction. Insufficient implementation due to a lack of understanding may result in the need for further improvements. This study aims to identify the key factors for assessing lighting that promote good health and well-being in built environments. Additionally, the goal is to develop a simplified tool for evaluating lighting in terms of its impact on occupants’ health and well-being, using Thailand’s SOOK Building Standard as a basis. The tool aims to require no extensive understanding of health-specific illumination standards. Nevertheless, it can still assess whether the lighting conditions in a certain region or design affect the health of the individuals in the building, according to health guidelines.We determine the key assessment factors by analyzing the specific requirements and criteria described for each measure in the research methodology process. We employed the relevant lighting measures for the calculations and used a climate-based computational simulation to calculate the average daylight illumination for the topic of daylighting. We employed the minimum thresholds for each requirement in the lighting measurement metrics to analyze a data range that satisfies the specified criteria, allowing us to verify additional measurement input data and identify any correspondences within the defined data range.The results illustrate the key assessment factors for the required inputs, which include both lighting and physical area measurements on-site. This research concentrates on addressing the implementation challenge, leading to the development of a prototype assessment tool that evaluates these measurement inputs and displays the overall score for each attribute of light and health, as per the SOOK Building Standard. The assessment tool’s development findings will encourage wider adoption of lighting design techniques in built environments. This will establish an environment that actively promotes and enhances human health and well-being.